Toward a Competitive Agent Framework for Magic: The Gathering - Chris Alvin; Michael Bowling; Shaelyn Rivers-Green; Deric Siglin; Lori Alvin (Proceedings of the International Florida Artificial Intelligence Research Society Conference, 2021)
Magic: The Gathering is a collectible card game that is traditionally a human-based game: two or more players compete with their own custom deck to eliminate their opponent(s). Magic has again surged in popularity with the release of Magic: Arena, a digital substitute for the physical card game. What Magic: Arena lacks is meaningful gameplay with a competitive, intelligent agent. We propose a strategy-based framework for basic decision making in Magic: The Gathering. We describe these procedures and provide experimental evidence for the effectiveness of our approach.